2008
DOI: 10.1111/j.1365-2710.2008.00957.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between a TGFβ1 promoter polymorphism and the phenotype of aspirin-intolerant chronic urticaria in a Korean population

Abstract: These findings suggest that the -509C>T polymorphism in the TGFbeta1 promoter may contribute to the development of the AICU phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 38 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…The nonsynonymous variant on the diamine oxidase gene (DAO rs10156191, p.Thr16Met) was moderately but significantly associated with cross-intolerance to NSAIDs (OR, 1.59; 95% CI, 1.27-2.00; P = 6 9 10 À5 for the minor allele) (45). In contrast, HNMT was the only significant predictor of this pathway in NAR to aspirin (32,33,36). Results from these studies suggest that mutations in genes encoding histaminemetabolizing enzymes may increase the risk, or modify the clinical presentation, of NAR, in which histamine plays an important role.…”
Section: Genetic Predictors Of Nar: the Examples Of Nonspecific Reactmentioning
confidence: 84%
See 2 more Smart Citations
“…The nonsynonymous variant on the diamine oxidase gene (DAO rs10156191, p.Thr16Met) was moderately but significantly associated with cross-intolerance to NSAIDs (OR, 1.59; 95% CI, 1.27-2.00; P = 6 9 10 À5 for the minor allele) (45). In contrast, HNMT was the only significant predictor of this pathway in NAR to aspirin (32,33,36). Results from these studies suggest that mutations in genes encoding histaminemetabolizing enzymes may increase the risk, or modify the clinical presentation, of NAR, in which histamine plays an important role.…”
Section: Genetic Predictors Of Nar: the Examples Of Nonspecific Reactmentioning
confidence: 84%
“…1). Among the 42 selected studies that reported genetic predictors in association with immediate-type hypersensitivity, 19 were related to BLs (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) (Table 1), 12 to aspirin (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) (Table 2), and eight to other NSAIDs (43-50) (Table 3). Three studies reported genetic predictors in association with biologicals, including hypersensitivity to asparaginase (51), EGF receptor inhibitors (52), and infliximab (53) ( Table 4).…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major allele frequency at TGFβ1 -509C>T was significantly higher in CU patients in an Iranian population 47. In contrast, the minor allele frequency of -509C>T was significantly higher in AICU patients in a Korean population, and this allele tended to be associated with a lower serum level of TGF-β1 48,49. The minor allele of this variant, TGFβ1 -509T, was identified as a risk factor in patients with AERD and asthma in two studies 49,50.…”
Section: The Candidate Gene Approach In Cumentioning
confidence: 92%
“…An additional 15 articles were excluded. Five did not report case–control studies, 10–14 three were not asthma studies, 15–17 three were family‐based studies, 18–20 two did not report useable data, 21,22 one was a repeat publication 23 and one reported on TGF‐β2 polymorphisms rather than TGF‐β1 polymorphism 24 . Therefore, 14 eligible articles reporting on TGF‐β1 polymorphisms, 7,25–37 and meeting the inclusion criteria, were identified.…”
Section: Resultsmentioning
confidence: 99%